Band energy approach and nonlinear optical phenomena in large-sized nanoparticles - Ivan V. Kityk (Journal of Telecommunications and Information Technology, 2006)
This report presents principal optical properties of semiconducting large-sized nanocrystalline (LSNC) material with thickness within 10–50 nm range. A quantitative parameter for description of the LSNC state is introduced. Influence of the surrounding polymer matrices on the properties of the LSNC is shown. Role of the surrounding polymer matrix background in the manifestation of material optoelectronic properties is studied. Superposition of long-range ordering with the localized nano-quantized effects is analyzed within a framework of different one-electron band energy approaches. Manifestation of the LSNC nonlinear optical (NLO) properties will be presented separately. It is clearly demonstrated that appropriate choice of LSNC geometry parameters together with proper modification of chemical composition could enhance the key NLO parameters.